The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14740/jh591
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of BCR-ABL1 Chronic Myeloid Leukemia in a JAK2-V617F Polycythemia Vera

Abstract: Emergence of a new chronic myeloid neoplasm in the setting of a previous one, or their concomitant appearance seems to be a rare event, but plenty of cases have been reported. We describe the case of a patient with JAK2-V617F polycythemia vera, which looses JAK2 clone and develops overt BCR-ABL1 chronic myeloid leukemia after 6 years. Once treatment with tyrosine kinase inhibitors controls BCR-ABL1 clone, JAK2 clone arises again. In this report, we review the literature and discuss the clonal relationship of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Through analysis of longitudinal samples in each individual case, they concluded that most instances of concurrent JAK2 V617F mutation and BCR-ABL1 fusion were actually composites of CML and BCR-ABL1 À MPN, and in some cases the second MPN was initially cryptic and became unmasked only after TKI treatment. This phenomenon of biclonal myeloproliferative processes (Figure 3, combination of routes 1 and 2) has been described in many case reports, 9,10,[12][13][14][15]17 and it seems to explain the pathologic evolution in patient 6 and possibly in patients 3 to 5 of our series. In patient 6, the BCR-ABL1 À MPN emerged only after CML declined to an undetectable level status after nilotinib therapy, reflecting an impact of clonal competition between the 2 MPNs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Through analysis of longitudinal samples in each individual case, they concluded that most instances of concurrent JAK2 V617F mutation and BCR-ABL1 fusion were actually composites of CML and BCR-ABL1 À MPN, and in some cases the second MPN was initially cryptic and became unmasked only after TKI treatment. This phenomenon of biclonal myeloproliferative processes (Figure 3, combination of routes 1 and 2) has been described in many case reports, 9,10,[12][13][14][15]17 and it seems to explain the pathologic evolution in patient 6 and possibly in patients 3 to 5 of our series. In patient 6, the BCR-ABL1 À MPN emerged only after CML declined to an undetectable level status after nilotinib therapy, reflecting an impact of clonal competition between the 2 MPNs.…”
Section: Discussionsupporting
confidence: 77%
“…A composite of the 2 neoplastic components is suggested by the cytogenetic study and molecular data for BCR-ABL1 and JAK2 V617F in patient 3. When BCR-ABL1 þ CML is present in conjunction with JAK2 V617F -positive MPN, it seems to play a dominant role compared with the JAK2 V617F clone, quickly replacing the latter before TKI treatment, 15,16 as seen in patients 4 and 5 in our series. Many times, effective treatment with TKI reverses the relative prevalence of the 2 clones.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The concomitance of CML and Ph-negative MPN has previously been reported and should be investigated to see if any aberrations indicating a Ph-negative MPN persist after a BCR-ABL1 transcript decline. 35,36 In summary, we showed that even analysis of more primitive populations does not provide improved somatic variant detection in either BCR-ABL1 or other genes recurrently mutated in other myeloid neoplasms. We have repeatedly demonstrated that BCR-ABL1 KD mutations are associated with failure events and do not hold prognostic value at diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…The only mutation in our present study that persisted at follow‐up was the MPN‐related JAK2 V617F mutation that was not present in T lymphocytes. The concomitance of CML and Ph‐negative MPN has previously been reported and should be investigated to see if any aberrations indicating a Ph‐negative MPN persist after a BCR‐ABL1 transcript decline 35,36 …”
Section: Discussionmentioning
confidence: 99%